REGIONALISMO PARANAENSE: DO ESBOÇO DE UMA SINOPSE DE HISTÓRIA REGIONAL DO PARANÁ À HISTÓRIA DO PARANÁ (1951-1969) - Almeida, Letícia Leal de (2016)
This work it is an analysis of the mobilization of the Regional Paraná history, tracing as a starting point the proposition Brazil Pinheiro Machado in Outline A Synopsis of Regional Paraná History (1951), and its relations with the speeches of 1960 in the books: General Courses: Agricultural Structures (1968) and History of Paraná (1969). From the speeches of Paraná intellectuals, Haughty Pilatti Balhana, Bento Munhoz da Rocha Netto, Brazil Pinheiro Machado and Cecilia Maria Westphalen, we understand the organization of a paranaense regionalism that brought together the three regions that make up the Paraná: Paraná Traditional, North and Southwest. In his texts, we understand the production of a memory and an identity for the Paraná 1960s, which tried to maintain regional cohesion, reducing tensions, while it did not cover all subjects, as mestizos, Indians and blacks, adopting a Eurocentric perspective of development and sought to project an image to Parana on the national scene. Clothed of scientific discourse authority from the Federal University of Parana, these texts constitute a framework of references to the history of Paraná, articulated a development project for the Paraná 1960s, due to the interests of the ruling classes, from which aimed to design the state towards progress